2023
DOI: 10.1029/2022ja031178
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Magnetic Dips on the Propagation of Electromagnetic Ion Cyclotron Waves

Abstract: Electromagnetic ion cyclotron (EMIC) waves are often observed in the terrestrial magnetosphere during a frequency range of 0.1-5 Hz (Anderson et al., 1992). Due to the major heavier ions, EMIC waves might mainly be divided into three bands (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 47 publications
(93 reference statements)
0
7
0
Order By: Relevance
“…Using ray‐tracing study, Horne and Miyoshi (2016) proposes that MS wave with a large WNA of 87° from outside of the plasmapause can reach where its frequency matches the local crossover frequency with a strictly parallel wave vector and converts to EMIC wave without energy attenuation at a low L‐shell ( L = 1.5), which could be a potential generation mechanism for EMIC waves of tens of Hz observed at low L‐shells. Recent investigation on the possibility of the mode conversion from MS wave to EMIC wave utilizing ray‐tracing and full‐wave simulation (Xu et al., 2023) supports the idea put forward by Horne and Miyoshi (2016). They demonstrate that MS waves may reach magnetic latitudes up to ±20° with wave normal angles of a wide range from perpendicular propagation to parallel propagation when approaching the local crossover frequency at low L‐shells ( L < 2.0).…”
Section: Introductionmentioning
confidence: 66%
See 2 more Smart Citations
“…Using ray‐tracing study, Horne and Miyoshi (2016) proposes that MS wave with a large WNA of 87° from outside of the plasmapause can reach where its frequency matches the local crossover frequency with a strictly parallel wave vector and converts to EMIC wave without energy attenuation at a low L‐shell ( L = 1.5), which could be a potential generation mechanism for EMIC waves of tens of Hz observed at low L‐shells. Recent investigation on the possibility of the mode conversion from MS wave to EMIC wave utilizing ray‐tracing and full‐wave simulation (Xu et al., 2023) supports the idea put forward by Horne and Miyoshi (2016). They demonstrate that MS waves may reach magnetic latitudes up to ±20° with wave normal angles of a wide range from perpendicular propagation to parallel propagation when approaching the local crossover frequency at low L‐shells ( L < 2.0).…”
Section: Introductionmentioning
confidence: 66%
“…Ray‐tracing study has shown that MS waves with the frequency several tens of Hz can propagate both near and off magnetic equator with various wave normal angles where their frequencies become very close to the local crossover frequency during their radially inward propagation (Horne & Miyoshi, 2016; Xu et al., 2023). In our full‐wave simulation, various latitudes, wave frequencies and wave normal angles are set as initial conditions for incident MS waves and how cold plasma can affect the subsequent propagation and mode conversion near the local characteristic frequencies is investigated by analyzing the spatial distribution of normalized wave intensity | S |/| S max | defined with time averaged Poynting vector obtained from simulation results.…”
Section: Simulation Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most representative examples of such magnetic field depletions are the so‐called magnetic dips, a spatially localized magnetic field depletion filled by hot injected ions (Xia et al., 2019; Zhu et al., 2021). Hot ions trapped within magnetic dips can generate EMIC waves (He et al., 2017; Yin et al., 2022; Yu et al., 2023). Such magnetic field depletions can change the radial gradient of the f pe / f ce ratio: for the dipole magnetic field f ce ∝ L −3 and empirical plasma density model (Sheeley et al., 2001) f pe ∝ L −2 , the ratio f pe / f ce ∝ L increases with radial distance.…”
Section: Spacecraft Observationsmentioning
confidence: 99%
“…In the unperturbed dipole magnetic field f ce ∝ L 3 and f pe ∝ L 2 (see the empirical model in Sheeley et al (2001)), which will give E ∝ L 1 with dE/dL < 0 (observed at larger L, around 06:47:30 UT). Substorm injections, however, transport hot ion populations (Birn et al, 2015;Gkioulidou et al, 2014Gkioulidou et al, , 2016Ukhorskiy et al, 2017Ukhorskiy et al, , 2018) that may form localized regions of magnetic field depletion (so-called magnetic dips, Xia et al, 2019;Zhu et al, 2021) filled by EMIC waves (see He et al, 2017;Yin et al, 2022;Yu et al, 2023;. This magnetic field depletion will result in a weaker radial gradient of f ce , that is f ce ∝ L 3+q with q > 0 ( Xia et al, 2019;Zhu et al, 2021), and this effect may make f ce /f pe ∝ L 1+q increase with decreasing L (i.e., dE/dL > 0, observed around 06:47:45 UT).…”
Section: First Event: Emic Wave-driven Precipitationmentioning
confidence: 99%